Bank Bailouts and Aggregate Liquidity - Diamond, Douglas W; Rajan, Raghuram G (American Economic Review, 2002)
the 2002 meetings of the American Economics Association. Governments sometimes bail out banks by recapitalizing them, or offering to insure their liabilities. The government’s goal may be to rescue borrowers, bankers, or depositors – and economists have developed rationales why each of these constituencies may merit protection (e.g., Diamond [2001)). These potential benefits have to be weighed against the costs of a bailout, which are typically thought to be those of the damage to long-run incentives that such intervention engenders. In this paper, we would like to present a different effect of bank bailouts: Bank bailouts alter the availability of aggregate liquidity in the economy. While a well-targeted bailout can help rescue an otherwise collapsing banking system (see Diamond-Rajan [2001a]), a poorly targeted bailout can even tip a banking system into a systemic crisis. This (ex-post crisis) cost of bank bailouts has, to the best of our knowledge, not been examined elsewhere, and is the focus of this paper. The Framework We consider a world with entrepreneurs, investors, and lenders. The economy lasts for two periods and three dates– date 0 to date 2. There are two kinds of goods in the economy-consumption goods and machinery. Each entrepreneur has a project, requiring 1 unit of